¿Tiene la justicia una sintaxis? - Winter, Steven L. (2020)
"Original title: Does Justice Have a Syntax? published in the Journal of Legal Education, vol. 69, no. 1 (Fall 2019); translated into Spanish by Victoria Perani. We thank the author and the Journal of Legal Education for permission to publish this article."